The osteology of the lacertid genus Darevskia Arribas, 1999 (Squamata, Lacertidae) - Arribas, Oscar (Zootaxa, 2024)
A total of 230 cleared and alizarin stained and 136 radiographed specimens of Darevskia belonging to 47 nominal taxa (species, subspecies or singular clades) including the seven parthenogenetic ones and a triploid hybrid were studied. Sixteen osteological characters in all the tried species were analyzed. These characters by corporal regions were: skull characters: 1.—number of premaxillary teeth; 2.—number of maxillary teeth; 3.—number of dentary teeth; 4.—teeth morphology; 5.—presence of anterolateral process in the postfrontal bone; 6.—presence of anteromedial process in the postorbital bone; 7.—comparative lengths of the postorbital and postfrontal bones; 8.—overlap degree between the postorbital and the squamosal bones. Postcranial characters: 9.—existence of visible (ossified) ribs associated with the third presacral vertebrae; 10.—sternal/xiphisternal costal formula and presence of inscriptional ribs; 11.—number of presacral vertebrae; 12.—number of posterior dorsal vertebrae (short presacral ribs); 13.—presence and form of the sternal fontanelle; 14.—form of the clavicles (emarginated or marginated); 15.—interclavicle form; 16.—morphology of first autotomic vertebrae of the tail. Our goals were to characterize osteologically the different species of Darevskia, to contrast their relationships traced from osteological traits with the available genetic-derived phylogenies of the group, to compare the osteological characteristics of the parthenogenetic species with their bisexual parental species, and to comment on their parentage and character polarity. Finally, we aimed to search for osteological characteristics of the different groups within Darevskia, diagnosing them for the first time. The results, commented on by characters, are available in the main text, and taxa characteristics are easily consultable and condensed in Table 1. Osteological characteristics of Darevskia, together with available phylogenetic trees, have permitted us to define some new groups within Darevskia (raddei, chlorogaster, defilippi, and parvula new groups) (Appendix 3), which are reciprocally monophyletic and have diagnostic characteristics. All of them are diagnosed and named as subgenera to be used if necessary, instead of the partial, old and not always comprehensive groups.